ANALISIS TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA DESA TERHADAP MANFAAT BAGI KESEJAHTERAAN MASYARAKAT DESA - Sri Wahyuni; Darmawan Sriyanto; Novi Mutiara (Universitas Muhammadiyah Bengkulu, 2023)
The purpose of this study is to determine the implementation of local government accountability, the implementation of the principles of accountability and transparency in government accountability and the obstacles faced, as well as to analyze the relationship between accountability and transparency in providing benefits to encourage the welfare of rural communities. Analysis method is used to evaluate research variables, multi-scale model is used to increase credibility and measurement accuracy. A five-stage Likert scale was used from strongly disagree to strongly agree. The questionnaire was built in accordance with the objectives and research variables. From the test results of the coefficient of determination of the need for variables obtained an Adjusted R Square value of 0.678, which means that transparency and accountability affect the management of village funds by 67.8%. While the remaining 32.2% is explained by other variables that are not used in this study.